Perceptions of “Srem Folk Fest” Participants According to Cultural Tourism Preferences - Timotijević, Srđan; Mijatov, Maja; Sekulić, Milena (Turizam, 2020)
Abstract “Srem Folk Fest” became one of the most popular and significant international folklore festivals in this part of the Balkan, since 2004. For past 16 years, Sremska Mitrovica was a host city for European, Asian, South American and African youth. Besides its historical importance, this city on the Sava river could also be considered as promoter of culture, tradition and folklore of its guests. Each year, the artistic stylization of folklore stage is accompanied by about 20.000 visitors during the four festival nights. In 2015, “Srem Folk Fest” was added to the calendar of events of the International Council of Organizations of Folklore Festivals and Folk Arts (CIOFF). The Festival is also recognized by the Serbian National Commission for UNESCO as the keeper of the intangible cultural heritage. One of the main tasks of the paper is related to the need of considering potential and participants’ intentions to  repeat their visits, as well as of improving the offer and promotion of the city and its surroundings. The aim of the paper is to analyze the data obtained in the context of the behavior and preferences of participants/respondents, to determine the specificity of their role and thus to make a recommendation for creating even better offer. The study obtained the survey research, while gained results might provide a good basis for further organization in accordance with their expectations. In addition, the results could also find practical implication in terms of providing basic information necessary to expand this event within the surrounding area of ​​Sremska Mitrovica.